School-based management practices and utilization of special education fund - Edwin T. Castillo; Maria Kristina M. Cay (International Journal of Educational Management and Development Studies)
This study assessed the School-Based Management (SBM) practices and the utilization of Special Education Funds (SEF) within the Department of Education, Quezon Division, focusing on the Tiaong I District in the Philippines. Guided by Musgrave's (1959) theory of public finance and Dalton's (1922) principle of maximum social advantage, the research employed a mixed-method explanatory sequential design. Data were gathered from 232 respondents using purposive sampling, with a validated questionnaire as the primary instrument. Quantitative analysis utilized Kruskal-Wallis to examine significant differences in SEF utilization across respondent profiles, and thematic analysis was conducted to identify challenges. Results revealed no statistically significant differences in SEF utilization across sex, age, educational attainment, or position (p > 0.05). Thematic analysis highlighted challenges such as underutilization in areas like the purchase of books and periodicals. Based on the findings, it is recommended that the Department of Education continue to monitor and optimize the allocation and utilization of SEF to ensure equitable resource distribution across various categories, with particular attention to underutilized areas such as the purchase of books and periodicals. This paper uniquely contributes to the field by providing a detailed examination of SEF utilization at the local level in the Philippines, offering insights into resource allocation consistency and identifying specific demographic needs for improved educational outcomes.